Predicting the most economical option of managing electric vehicle battery at the end of its serviceable life - Lewis Parkinson; Wai Ming Cheung (Cleaner Engineering and Technology)
It is predicted that millions of electric vehicle batteries (EVBs) will retire in the next decade. With the global Electric Vehicles (EVs) market share increasing to over 40 million by 2030, the replacement of unwanted EVBs will become more abundant and may end up in landfills. These discarded EVBs can become a threat to the environment and to human health if they are not treated, disposed of, and recycled appropriately. Numerous end-of-life (EOL) cost estimation methods that have been developed are mainly for evaluating fossil fuel vehicle components. Research within the scope of EOL of EVBs however, is slow in progress, therefore, this work focuses on developing a cost estimation method for predicting EOL costs of EVBs by adopting a circular economy approach. This proposed method is validated through a case study using two Nissan's EV battery packs. The significance of this study may provide valuable information which could, indirectly lead to the redesign of EVBs for better business circular economy and less waste pollution for future EVs. The main results show that the potential economic benefit that generated by reusing/repurposing EOL EVBs is 92% more profitable than recycling and 52% more profitable than remanufacturing. This study concludes that reuse/repurpose becomes the most profitable process when EVBs reach the end of their serviceable life. Remanufacturing method can also be economically viable if it considers multi-cell replacement of an EVB.